2022
DOI: 10.3390/ijms23073796
|View full text |Cite
|
Sign up to set email alerts
|

ABA Mediates Plant Development and Abiotic Stress via Alternative Splicing

Abstract: Alternative splicing (AS) exists in eukaryotes to increase the complexity and adaptability of systems under biophysiological conditions by increasing transcriptional and protein diversity. As a classic hormone, abscisic acid (ABA) can effectively control plant growth, improve stress resistance, and promote dormancy. At the transcriptional level, ABA helps plants respond to the outside world by regulating transcription factors through signal transduction pathways to regulate gene expression. However, at the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 88 publications
(106 reference statements)
0
21
0
Order By: Relevance
“…Plants are exposed to a variety of environmental conditions that negatively impact their physiology and yields (Rivero et al, 2022;Sharma et al, 2022;Zandalinas and Mittler, 2022). Several studies identified mechanisms involving genes, proteins, and metabolites that underlie plant responses to stress conditions (Chen et al, 2022;Hassan et al, 2022;Huang et al, 2022;Mittler et al, 2022;Yang et al, 2022;Zhan et al, 2022). Some of these molecules were used to improve plant responses to abiotic and biotic stresses (Li et al, 2022;Mahto et al, 2022;Wang and Komatsu, 2022;Zhao et al, 2022).…”
Section: Editorial On the Research Topic Structural Bioinformatics An...mentioning
confidence: 99%
“…Plants are exposed to a variety of environmental conditions that negatively impact their physiology and yields (Rivero et al, 2022;Sharma et al, 2022;Zandalinas and Mittler, 2022). Several studies identified mechanisms involving genes, proteins, and metabolites that underlie plant responses to stress conditions (Chen et al, 2022;Hassan et al, 2022;Huang et al, 2022;Mittler et al, 2022;Yang et al, 2022;Zhan et al, 2022). Some of these molecules were used to improve plant responses to abiotic and biotic stresses (Li et al, 2022;Mahto et al, 2022;Wang and Komatsu, 2022;Zhao et al, 2022).…”
Section: Editorial On the Research Topic Structural Bioinformatics An...mentioning
confidence: 99%
“…Abscisic acid (ABA) is a very important plant hormone, and has been shown to regulate many aspects of plant growth and development including leaf senescence, seed dormancy, embryo maturation, and responses to drought and other environmental stresses [ 27 , 28 , 29 ]. Several genes from HD-Zip I are demonstrated to be involved in the ABA signaling pathway and in the regulation of plant developmental adaptation to environmental stresses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, the original research articles investigate the effects of ABA on epicuticular wax metabolism regulation in a citrus fruit cultivar [ 9 ], the regulation of WNK kinases and their comprehensive interaction with ABA components [ 10 ], CCD family members in poplar and their expression patterns in response to ABA and abiotic stress [ 11 ], the molecular function of NAC transcription factor PwNAC11 in drought stress [ 12 ], the interaction between AFPs and DELLA proteins [ 13 ], and the molecular mechanism by which AGB1 regulates the GA pathway in Arabidopsis [ 14 ]. The reviews published in this Special Issue focus on how ABA regulates plant development and stress tolerance through alternative splicing [ 15 ], the mechanisms of ABA-mediated drought stress responses in plants [ 16 ], the roles of ABA and GA in stem/root tuber development [ 17 ] and the molecular mechanisms underlying ABA and GA regulation of seed development from embryogenesis to maturation [ 18 ]. In this editorial, I sum up the most significant findings of these insightful works.…”
mentioning
confidence: 99%
“…However, the mechanisms by which ABA can regulate plant development and tolerance to abiotic stress by mediating AS are not well understood. Yang et al [ 15 ] reported in their review that ABA mediates plant abiotic stress tolerance and development, particularly through AS events. First, the authors briefly revised the main roles of ABA in abiotic stress response, the regulatory network of ABA signaling and ABA functions in development by focusing on seed germination and flowering.…”
mentioning
confidence: 99%
See 1 more Smart Citation